Degradation observations of encapsulated planar CH3NH3PbI3 perovskite solar cells at high temperatures and humidity. Issue 15 (21st April 2015) - Han, Yu; Meyer, Steffen; Dkhissi, Yasmina; Weber, Karl; Pringle, Jennifer M.; Bach, Udo; Spiccia, Leone; Cheng, Yi-Bing
<x xml:space="preserve">Abstract</x> The stability of encapsulated planar-structured CH3NH3PbI3 (MAPbI3) perovskite solar cells (PSCs) was investigated under various simulated environmental conditions.